2016
DOI: 10.5301/heartint.5000231
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Daily Physical Activity in Individuals with Heart Failure

Abstract: BackgroundPrevious studies indicate that seasonal variation affects daily physical activity (PA), but none have investigated this relationship in individuals with heart failure (HF) who also have implanted cardioverter defibrillators and cardiac resynchronization therapy (ICD/CRT) devices. The purpose of the present study was to determine if seasonal variation in temperature affects daily PA in patients with HF and ICD/CRTs.Patients and methodsSecondary analysis of data from 16 subjects with HF and Medtronic® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
2
16
0
1
Order By: Relevance
“…Our study showed that daily step was lower by 27% in the winter season compared with the spring season. These findings are consistent with previous studies that showed the association between daily PA and the season [8,[27][28][29][30]. Those studies observed that PA decreased during the winter season in healthy adults [8] and elderly subjects [29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that daily step was lower by 27% in the winter season compared with the spring season. These findings are consistent with previous studies that showed the association between daily PA and the season [8,[27][28][29][30]. Those studies observed that PA decreased during the winter season in healthy adults [8] and elderly subjects [29].…”
Section: Discussionsupporting
confidence: 93%
“…In the spline regression models, the relationship between wind chill temperature and daily steps was linear below 25 • C wind chill temperature, with lower daily steps corresponding to colder temperatures. This is similar to the previous findings [30,39]. The wind chill temperature used in our study is likely to be more closely related to patients' PA behavior compared to absolute temperature, as the wind chill temperature is a quantitative measure of the heat or cold that the human body feels, calculated based on air temperature and wind velocity [40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…D‐PA data are increasingly being used to understand patterns of activity engagement after ICD implantation; however, investigators have varied in the approach taken to calculate the baseline level of D‐PA, making it difficult to compare findings across studies. In some studies, baseline is defined as average activity over a period of several days, 1 to 2 weeks after CIED implantation, to account for procedural recovery time; in other studies, baseline is defined as average activity over 7 to 30 days, 1 to 2 months after implantation .…”
Section: Resultsmentioning
confidence: 99%
“…Sob os pontos de vista físico e fisiológico, o envelhecimento caracteriza-se por uma degeneração gradual e progressiva dos órgãos, tecidos e metabolismo, acarretando a atenuação de suas funções [3]. Sabe-se que a debilidade do organismo no combate às enfermidades é acentuada pelos fatores sazonais, geralmente acarretando um aumento na procura por serviços de saúde durante os períodos frios do ano [3][4][5][6][7].…”
Section: Introductionunclassified